Estudo do desempenho da sinalização horizontal a frio em vias urbanas recém recapeadas no município de Fortaleza - Rodrigues, Marcelo Fortuna França (2013)
The use of cold painting on horizontal signs in urban driveways is very common worldwide, as also in Brazil. In Fortaleza City, the cold paintings are used in almost all paved driveways. During maintenance, recovery, or reconstruction practices, it has been observed that the lengths of the horizontalsings are not matching the expectations provided by their manufacturers. Even complying with the technical standards and the product user’s guide, and using tested and approved materials,the horizontal paintings have been largely underperformed. This dissertation investigates some features that may be influencing this reduced length of the horizontal signs, such as the curing time of the asphalt mix, which showed to influence positively the measures of Reflectivity of Pavement Markings.